Care for end-stage kidney disease in China: progress, challenges, and recommendations - Tiange Chen; Xuefeng Sun; Sian Tsuei; Ruirui Yang; Winnie Yip; Hongqiao Fu (The Lancet Regional Health. Western Pacific)
Summary: This review comprehensively evaluates China’s progress in care of end-stage kidney disease (ESKD) by identifying achievements and gaps, reviewing ESKD-related policy initiatives, and proposing policy recommendations. In the past decade, China has made laudable progress in access to ESKD care with narrowed difference between the number of patients needing and receiving kidney replacement therapies (KRT). China has also experienced significant improvements in clinical quality and outcomes of ESKD care. These achievements stem from concerted efforts in advocating effective policies, increasing fiscal subsidies, re-designing health insurance schemes, encouraging healthcare delivery from both public and private sectors, and improving quality regulation. However, challenges remain, including inequitable access to care across regions and groups, and suboptimal quality and outcomes in some underdeveloped areas. To address these gaps, we recommend reforming the financing policy, adopting quality-based payment methods, strengthening quality monitoring system, improving chronic kidney disease prevention and management, and developing alternative KRT modalities.